2022
DOI: 10.3389/fnagi.2022.955919
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Parkinson’s disease and gastrointestinal diseases

Abstract: An increasing number of studies have provided evidence for the hypothesis that the pathogenesis of Parkinson’s disease (PD) may derive from the gut. Firstly, Lewy pathology can be induced in the enteric nervous system (ENS) and be transported to the central nervous system (CNS) via the vagal nerve. Secondly, the altered composition of gut microbiota causes an imbalance between beneficial and deleterious microbial metabolites which interacts with the increased gut permeability and the gut inflammation as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Meanwhile, multiple cohort studies ( 99 102 ) and two systematic reviews and meta-analysis ( 103 , 104 ) have found that irritable bowel syndrome (IBS) is associated with a higher hazard of PD. IBS is a functional bowel disorder characterized by recurrent abdominal pain and changes in bowel habits ( 105 , 106 ). It has been found that intestinal inflammation, increased intestinal permeability and changes in intestinal microbiome are involved in the pathogenesis of IBS, which was similar to that of PD ( 107 ).…”
Section: Intestinal Microbiome Dysregulation and Intestinal Inflammationmentioning
confidence: 99%
“…Meanwhile, multiple cohort studies ( 99 102 ) and two systematic reviews and meta-analysis ( 103 , 104 ) have found that irritable bowel syndrome (IBS) is associated with a higher hazard of PD. IBS is a functional bowel disorder characterized by recurrent abdominal pain and changes in bowel habits ( 105 , 106 ). It has been found that intestinal inflammation, increased intestinal permeability and changes in intestinal microbiome are involved in the pathogenesis of IBS, which was similar to that of PD ( 107 ).…”
Section: Intestinal Microbiome Dysregulation and Intestinal Inflammationmentioning
confidence: 99%
“…Systemic and fecal inflammatory markers IFN-γ, TNF-α, and neutrophil gelatinase-associated lipocalin were also associated with an elevated expression of Bacteroides and Bifidobacterium in PD patients [ 41 ]. Thus, the intestinal microbiota composition in PD patients appears to influence pharmacological treatment responses [ 135 ].…”
Section: The Possible Role Of the Enteric Nervous System In Parkinson...mentioning
confidence: 99%
“…Indeed, PD is characterized by motor features and numerous non-motor symptoms that include sensory abnormalities, fatigue, sleep disturbances, autonomic dysfunction, psychiatric disorders (depression, anxiety, and apathy), and others [ 32 , 36 , 37 , 38 ]. Orthostatic hypotension, urogenital system disorders, hypersalivation, swallowing impairment, delayed gastric emptying, and constipation are the common manifestations related to autonomic dysfunction in PD [ 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Constipation is one of the most frequent non-motor symptoms, affecting up to 80% of PD patients, and may precede the onset of motor symptoms by years [ 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that young adult CD brain changes may resemble brains older healthy adults ( Nair et al, 2019 ), perhaps due to the increase of proinflammatory cytokine exposure in both aging adults and CDs. Additionally, IBD has been associated with age-related diseases such as, Parkinson’s ( Lin et al, 2016 ; Brudek, 2019 ; Zeng et al, 2022 ) and Alzheimer’s disease ( Hillary et al, 2020 ; Wang et al, 2022 ). To date, no studies have demonstrated similarities between morphological brain changes seen in IBD and brain morphometry observed in older healthy controls.…”
Section: Introductionmentioning
confidence: 99%